Texting in the Fourth Trimester: mHealth for Postpartum Care - Bogaert, Kelly C.; Kaplowitz, Elianna; Atreja, Ashish; Afzal, Omara (American Journal of Perinatology, 2024)
Rising maternal morbidity and mortality in the United States is a complex problem and is often tied to the postpartum period. Postpartum visits are poorly attended leading to gaps in contraception, mental health care, and care for chronic conditions. mHealth, health care supported by mobile technologies, has been shown to improve antenatal care adherence. Our study aims to determine whether an mHealth intervention of interactive, educational text messages can improve care for women postpartum.We conducted a randomized control trial of 191 women receiving OB/GYN care in our clinic from November 2019 to April 2020. Patients were randomized postpartum to receive either routine care or routine care with mHealth text messages and appointment reminders specific to delivery type. The primary endpoint was attendance at the 6-week postpartum visit with secondary endpoints of breastfeeding, contraception use, emergency visits, and postpartum depression scores (Edinburgh Postnatal Depression Scale). A subgroup analysis was additionally conducted to assess the impact of some visits shifting to telehealth due to the timing of the coronavirus disease 2019 (COVID-19) pandemic.Patient demographics were similar between the two groups. There was no significant difference in postpartum appointment attendance between text messages (n = 57, 59%) and control groups (n = 62, 66%; p = 0.31). In total, 117 patients were scheduled for in-person postpartum visits, and 74 for telehealth visits during the COVID-19 pandemic, with no significant difference in attendance rate between groups for either visit modality.Automated text messages alone did not increase our primary outcome of adherence to postpartum care, even when visits were conducted by telehealth. While mHealth has proven successful in other care areas, such as antepartum follow-up, further research is needed to determine whether it is an effective method to improve adherence to postpartum care, or whether other strategies must be developed, including augmentation with human navigators.
Keywords: mHealth; texting; fourth trimester; maternal morbidity; maternal mortality; adherence